Institutional Capacity of Forest Village Community of Meru Betiri National Park - Diah Puspaningrum; Ati Kusmiati (Sekolah Pascasarjana Universitas Brawijaya, 2018)
The empowerment of community at buffer zone of conservation area is an effort to improve community capacity, as individual and group, in managing resources potential as well as their problems in order to improve independency, prosperity and life quality of the community at buffer zone of conservation area by maintaining the sustainability of the area. The aims of the research were: (1) to find out the capacity of Conservation Forest Village Community Institution (Lembaga Masyarakat Desa Hutan Konservasi-LMDHK) as an entry point in empowerment; and (2) to find out community participation especially the members of institution in empowerment program. The research used qualitative approach to analyze empowerment conducted on forest village community institution at conservation area of Meru Betiri National Park. Primary and secondary data sources were used with data collection method of observation, in-depth interview and focus group discussion (FGD) and RRA (Rapid Rural Appraisal) method. Data analysis method used was interactive model from Miles and Hubberman (1992). Research result indicates that (1) the condition of institutional capacity of village community at buffer zone of conservation area based on: a) leadership in the institution; b) specification of values and goals; c) operational method and action in the implementation of program related to the function of institutions; and d) the formation of internal structure and institutional maintenance had not achieved as expected; (2) the form of participation of village community of buffer zone of conservation area was in the level of consultation and the highest was in the level of placation. Manipulation and therapy were in the level of â€œnon-participationâ€, whereas, the level of participation of the community was in the level of tokenism.